The Effect of Habits of Mindo n Junior High School Students’ Mathematics Communication Ability - Veni Aprilia Dwi Astuti; Yuliani, Anik (IKIP Siliwangi, 2024)
This research aims to determine the effect of habits of mind on junior high school students' mathematical communication skills on triangles and quadrilaterals. Habits of Mind is defined as a habit of thinking that is carried out as an intelligent behavior pattern when faced with a problem whose solution isn’t easily known so that productive action occurs. The problem in this research is motivated by its importance habits of mind in learning mathematics and improving students' mathematical abilities. The method used in this research is method ex post facto. The population in this study were all class VIII students in one of Junior High Schools in Karawang Regency. The sample in this study was 42 students using the technique purposive sampling. The instrument used in this research is a test, namely mathematical communication skills which consists of 5 (five) description questions. Apart from that, it also uses non-test instruments in the form of questionnaires habits of mind which consists of 30 statements. Data analysis was carried out using simple linear regression techniques. The research results obtained a linear regression equation Y = -25.065 + 1.345X. The magnitude of the correlation coefficient r2 = 0.848 and coefficient of determination = 84.8%. This shows that there is habits of mind had an influence on students' mathematical communication skills of 84.8%, while 15.6% was influenced by other factors not measured in this research.